Analisis Pengelolaan Gudang dengan Metode FIFO untuk Mendukung Efektivitas Distribusi pada PT SID Cabang Sidayu Gresik - M. Wasiur Riski; Siti Nursyamsiah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines warehouse management and the implementation of the First In First Out (FIFO) method in supporting distribution effectiveness at PT Semen Indonesia Distributor (SID), Sidayu Gresik Branch. Using a descriptive qualitative approach, data were collected through interviews and observations involving the Person in Charge of Operations, Branch Administration Officer, and Warehouse Checker. The findings indicate that warehouse activities are systematically managed through structured receiving, storage, and distribution procedures. FIFO implementation, supported by arrival-date labeling, improves inventory turnover, maintains cement quality, minimizes prolonged storage risks, and facilitates distribution. Overall, effective warehouse management and FIFO implementation strengthen distribution effectiveness. Keywords: Warehouse Management; FIFO (First in First Out); Distribution Effectiveness; Inventory